Development of interactive multimedia based on articulate storyline to improve students' creative thinking skills on support solution materials - Ananda, Wulan Rizqi; Iriani, Rilia; Hamid, Abdul (IAIN Palangka Raya, 2024)
This research aims to create a product in the form of interactive multimedia based on an articulate storyline using buffer solution material that is feasible, practical, and effective for improving students' creative thinking skills. The research method used in this development is Research and Development (R&D) with a development model, namely 4D: define, design, develop, and disseminate. Interactive multimedia based on an articulate storyline was tested on 34 class XI MIPA 1 MAN 2 Banjarmasin City students. The research results indicate that interactive multimedia based on an articulate storyline has been developed: (1) Worthy in terms of the appropriateness of content, language, visual appearance, audiovisual, and application; (2) Very practical in individual trials and small group trials; (3) Very practical from the students' responses and very good from the teacher's teaching activities; (4) Effective based on the N-gain value of students' creative thinking skills is in the medium category. Interactive multimedia based on an articulate storyline in buffer solution material to improve students' creative thinking skills is declared feasible, practical, and effective.